Development of novel seminested polymerase chain reaction assays for detecting toxigenic Vibrio cholerae and Shigella spp. in water - Venter, S.N. (Stephanus Nicolaas) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2001.